LDC-LaAlO3 composite electrolyte material, preparation method thereof and semiconductor ion fuel cell
Through the LDC-LaAlO3 composite electrolyte material, the problems of reduced conductivity and internal short circuit of solid oxide fuel cells at low temperatures are solved, efficient electrochemical performance improvement is achieved, and its commercial application potential is expanded.
Patent Information
- Application Number
- CN202411092998.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-09
- Publication Date
- 2024-12-13
AI Technical Summary
The catalytic activity of existing solid oxide fuel cells decreases at low temperatures, resulting in a decrease in ionic conductivity and may cause internal short circuits, affecting battery performance.
The LDC-LaAlO3 composite electrolyte material is used to mix La3+ doped CeO2 and LaAlO3, and ultrafine electrolyte powder is prepared by glycine nitrate method, oxygen ion vacancies are introduced and the short-circuit problem of CeO2 electrolyte is suppressed, and the battery power density is improved.
It significantly improves the conductivity and electrochemical performance of low-temperature solid oxide fuel cells, extends the potential of the battery's commercial application, and improves the working efficiency of the fuel cells.
Smart Images

Figure CN119133540A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid oxide fuel cells, and more specifically, to an LDC-LaAlO3 composite electrolyte material and a preparation method thereof, and a semiconductor ion fuel cell. Background Art
[0002] Solid Oxide Fuel Cell (SOFC) is a clean and efficient green energy conversion technology. The current main research goal is to reduce the operating temperature. However, when the operating temperature of SOFC is reduced, its catalytic activity will also be greatly reduced, resulting in a decrease in ionic conductivity.
[0003] Semiconductor ion fuel cell (SIFC) is a SOFC that uses a semiconductor and ion conductor composite as the electrolyte. The internal heterogeneous structure of the electrolyte improves the electrochemical performance of the battery at low temperatures (450-600°C) and is considered to be a potential battery for commercialization.
[0004] At present, the commonly used SIFC electrolyte materials are mainly CeO2 electrolyte materials, which show excellent electrochemical performance in the low temperature region. However, due to the CeO2 in the H2 reducing atmosphere, Ce 4+ Easily reduced to Ce 3+ , and accompanied by the generation of electronic conductance, these additional electronic conductances may cause internal short circuits and lead to significant reductions in opening voltage and power.
[0005] Therefore, how to provide a new solid oxide fuel cell electrolyte material so that the battery has excellent conductivity at low temperatures and SIFC has better battery performance is an urgent problem that needs to be solved. Summary of the invention
[0006] In view of this, one of the objects of the present invention is to provide a composite electrolyte material suitable for semiconductor ion fuel cells. The composite electrolyte material provided by the present invention has very beneficial performance in low-temperature solid oxide fuel cells (LT-SOFC) and has broad application potential in the commercialization of SOFC.
[0007] To achieve the above object, the technical solution of the present invention is as follows: A LDC-LaAlO3 composite electrolyte material, the composite electrolyte material is used as an electrolyte for a semiconductor ion fuel cell, the composite electrolyte material is obtained by mixing LDC and LAO3, the LDC is La 3+The doped CeO2, the LAO3 is LaAlO3, and the mixing mass ratio of the LDC and LAO3 is 5~9:1~5.
[0008] LDC is Ce 0.8 La 0.2 O 2-δ , where δ is the value that keeps the compound electrically neutral.
[0009] The present invention selects La 3+ Doped CeO2 (LDC) was studied as a new type of electrolyte for SOFC, and ultrafine electrolyte powder LDC was prepared by glycine nitrate method.
[0010] At the same time, the introduction of LAO3 perovskite material on the basis of LDC electrolyte can promote the generation of oxygen ion vacancies at the interface O 2- While conducting, a high potential energy barrier can also be introduced to suppress the short-circuit problem of CeO2 electrolyte, effectively improving the battery power density.
[0011] Furthermore, the LDC and LAO3 mixing mass ratio is 6-8:2-4, preferably 7:3. The La 3+ The doping ratio of CeO2 does not exceed 30%, and the preferred doping ratio is 20%.
[0012] Furthermore, the mixing mass ratio of LDC and LAO3 is 7:3.
[0013] A second object of the present invention is to provide a method for preparing the above-mentioned composite electrolyte material, comprising the following steps: (1) Preparation of LDC: Weigh the raw materials Ce salt, La salt and glycine; Mix Ce salt, La salt, glycine and water, heat and stir to mix until the reaction liquid becomes viscous and finally produces powder with flame; collecting the powder, and sintering the powder to obtain LDC powder; (2) Preparation of LAO3: Weigh Al salt, La salt, EDTA and citric acid; Place Al salt, La salt, EDTA and citric acid in a container, add water, stir to dissolve, heat the water area and stir, adjust the pH value of the solution to 6-7, at which point the precipitate is completely dissolved; When the solution becomes viscous like a gel, it is dried, ground once, pre-calcined, ground twice, and sintered to obtain LAO3 powder; (3) Synthesis of LDC-LaAlO3 composite electrolyte materials Weigh LDC powder and LAO3 powder according to the mass ratio; The LDC and LAO3 materials were dissolved in ethanol, and then ball-milled, dried and ground to obtain the LDC-LaAlO3 composite electrolyte material.
[0014] Furthermore, in step (1), the Ce salt is Ce(NO3)3·6H2O, the La salt is La(NO3)3·6H2O, the molar ratio of glycine to metal ions is 1-1.5:1, preferably 1.2:1; and the metal ions are the sum of Ce ions and La ions.
[0015] Furthermore, in step (1), the heating temperature is 200-230°C, the sintering temperature is 750-850°C, and the sintering time is 1.5-3h.
[0016] Furthermore, in step (2), the Al salt is Al(NO3)3·9H2O, the La salt is La(NO3)3·6H2O, and the molar ratio of the sum of the Al ions and the La ions to the citric acid and EDTA is 1:1.5:1.5.
[0017] Furthermore, in step (2), the water area heating temperature is 70-85°C; the drying temperature is 200-230°C, and the drying time is 4-6 hours; the pre-firing temperature is 450-550°C; the sintering temperature is 1200-1300°C, and the sintering time is 4-6 hours.
[0018] Furthermore, in step (3), the ball milling speed is 180-200 r / min, and the ball milling time is 4-6 h.
[0019] The present invention also aims to provide a semiconductor ion fuel cell containing any of the above-mentioned LDC-LaAlO3 composite electrolyte materials.
[0020] Furthermore, the electrode material of the semiconductor ion fuel cell is LiNi 0.8 Co 0.15 Al 0.05 O2, the LiNi 0.8 Co 0.15 Al 0.05 O2 is commercially available; LiNi 0.8 Co 0.15 Al 0.05 O2 is mixed with pinene alcohol, alcohol and PVB to obtain NCAL slurry, which is then applied to nickel foam to obtain the electrode of the semiconductor ion fuel cell.
[0021] Compared with the prior art, the present invention has the following advantages: In the present invention, LDC-LaAlO3 composite electrolyte is synthesized by solid phase method. The composite of ultra-wide bandgap oxide LAO3 and LDC can increase the open circuit voltage of the fuel cell and accelerate the ion transmission rate, significantly improving the working efficiency of the fuel cell. This shows that the constructed LDC-LaAlO3 heterostructure electrolyte has very beneficial performance in LT-SOFC and has broad application potential in SOFC commercialization. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 In the embodiment of the present invention, different La 3+ IV and IP characteristic curves of doping ratio batteries tested at 550 ℃.
[0023] Figure 2 1 is the XRD diagram of LDC, LAO3 and LDC-LAO3 composite materials in the embodiments of the present invention, wherein: (a) LDC; (b) LAO3; (c) LDC-LAO3; Figure 3 is a SEM image of the LDC powder synthesized in Example 1 of the present invention; Figure 4 (a) cross-sectional SEM image and (b) contact surface SEM image of a single cell of the 7LDC-3LAO3 composite electrolyte in an embodiment of the present invention after testing; Figure 5 The IV and IP characteristic curves of the composite electrolyte batteries with different ratios in the embodiments of the present invention tested at 550°C, 500°C, 450°C and 400°C respectively; among them, (a) 5:5; (b) 6:4; (c) 7:3; (d) 8:2; (e) 9:1; (f) IV / IP curves of different mass ratios at 550°C; Figure 6 : is the electrochemical impedance spectra in the embodiment of the present invention, wherein: (a) the electrochemical impedance spectra of batteries with different composite ratios tested at 550 °C; (b) the electrochemical impedance spectra of 7LDC-3LAO3 tested at 550 °C, 500 °C, 450 °C and 400 °C respectively; Figure 7 It is the ionic conductivity curve of LDC-LAO3 with a mass ratio of 7:3 and pure LDC electrolyte at 550°C, 500°C, 450°C, and 400°C in the embodiment of the present invention. DETAILED DESCRIPTION
[0024] Many specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar modifications without violating the connotation of the present invention, so the present invention is not limited to the specific implementation disclosed below.
[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0026] Example 1 Synthesis of LDC Materials Ce was prepared as follows 0.8 La 0.2 O 2-δ (La 3+ 20% doped LDC) material: Ce(NO3)3·6H2O, La(NO3)3·6H2O and glycine were used as raw materials, the molar ratio of glycine to metal ions (the sum of Ce and La) was 1.2:1, and Ce(NO3)3·6H2O, La(NO3)3·6H2O and glycine were weighed by an electronic balance.
[0027] According to the equation: 0.8Ce(NO3)3+0.2La(NO3)3+XC2H5NO2+YO2→ Ce 0.8 La 0.2 O 2-δ +N2+H2O+CO2 Synthesis of 0.05 molCe 0.8 La 0.2 O 2-δ 7.0085 g of glycine (C2H5NO2), 17.3688 g of Ce(NO3)3·6H2O, and 4.3301 g of La(NO3)3·6H2O are required.
[0028] Put the drugs in a beaker in turn, add deionized water, place the beaker on a magnetic stirrer, and stir at 220°C to mix them thoroughly. As the stirring time increases, the clear liquid gradually becomes viscous, and finally the powder is ejected along with the flame to release a large amount of heat energy. After a while, collect the prepared powder. Sinter the powder at 800°C for 2h to obtain the prepared LDC2 powder.
[0029] According to the above steps, LDC1 (La 3+ doped 0.1), and LDC3 (La 3+ Doping 0.3).
[0030] The corresponding solid fuel cells were prepared with CeO2, LDC1, LDC2 and LDC3 as electrolytes, and the performance tests were carried out. The results are as follows Figure 1 shown.
[0031] It can be observed that La 3+ When the doping ratio is 0.1 and 0.3, the open circuit voltage is 1.098 V and 1.106 V respectively, and the output power density is 800 mW·cm -2 Left and right, and La 3+ The LDC electrolyte with the optimal doping ratio of 0.2 has the highest output power of 859 mW cm -2 The open circuit voltage at this time is 1.085 V, which is 722 mW·cm -2 The output power is increased by 18.9%.
[0032] In the subsequent embodiments, La 3+ The LDC electrolyte was tested with an optimal doping ratio of 0.2.
[0033] Example 2 Synthesis of LaAlO3 material LAO3 material was prepared by sol-gel method using Al(NO3)3·9H2O, La(NO3)3·6H2O, EDTA and citric acid as raw materials. Al(NO3)3·9H2O and La(NO3)3·6H2O were weighed by electronic balance according to the stoichiometric ratio of LAO3, and citric acid and EDTA were weighed according to the molar ratio of 1.5:1.5:1 with metal ions.
[0034] Specifically, to synthesize 0.02 mol of LaAlO3 material, 7.5026 g of Al(NO3)3·9H2O is required. La(NO3)3·6H2O 8.6602g, citric acid 12.6084g, EDTA 17.5344g.
[0035] Put the drug in a large beaker, add deionized water to fully dissolve it, place the beaker in a constant temperature water bath, set the temperature to 80 ℃ and stir evenly. Add ammonia water drop by drop to adjust the pH value of the solution. When the pH value is adjusted to 6~7, the precipitate is completely dissolved. When the solution is viscous to gel, take out the beaker and put it in an oven at 220 ℃ for 5h. Take out the beaker, grind the material thoroughly, put it in a muffle furnace and pre-burn it at 500 ℃ to remove organic matter. Grind the pre-burned material, then sinter it at 1300 ℃ for 5h, and finally grind it to obtain LAO3 powder.
[0036] Example 3 Synthesis of LDC-LaAlO3 composite electrolyte material The LDC material prepared in Example 1 and the LAO3 material prepared in Example 2 were prepared into a composite electrolyte by a solid phase method.
[0037] According to the five different mass ratios of LDC and LAO3, namely 9:1, 8:2, 7:3, 6:4, and 5:5, weigh LDC and LAO3 electrolytes and put them into a ball mill, and add an appropriate amount of alcohol to dissolve them. Set the ball mill to grind at a speed of 180 revolutions per minute for 5 hours. Put the ground material into a beaker with a syringe and dry it with a baking lamp. Grind the dried medicine in a mortar to obtain a composite electrolyte material, and finally store it in a test tube.
[0038] The 9LDC-1LAO3 composite electrolyte, the 8LDC-4LAO3 composite electrolyte, the 7LDC-3LAO3 composite electrolyte, the 6LDC-4LAO3 composite electrolyte and the 5LDC-5LAO3 composite electrolyte were obtained.
[0039] Example 4 Preparation of electrodes Prepare according to the following steps: S1. According to the ratio of 10g NCAL to 3mL pinene alcohol, 2mL alcohol, and 0.05g PVB, weigh an appropriate amount of NCAL (LiNi 0.8 Co 0.15 Al 0.05 O2), terpineol, alcohol, and PVB are put into a mortar and fully ground to make them evenly mixed to make NCAL slurry; S2. Use a punch to press the nickel foam into uniform round foam; S3, evenly apply NCAL slurry on the nickel foam, completely covering the nickel foam until no pores appear; S4. Wrap the coated nickel foam with tin foil and put it in the oven to dry; S5. Repeat S3 and S4 three times to make the NCAL electrode material fully and evenly cover the nickel foam, and then put it into the oven to dry thoroughly.
[0040] Example 5 Preparation of battery Prepare according to the following steps: The electrode prepared in Example 4 is placed in the bottom of the tablet pressing mold; Weigh about 0.3 g of the electrolyte composite material LDC-LAO3 (including multiple mixing ratios) obtained in Example 3 using an electronic balance, pour it into a mold, and flatten it; Put another prepared NCAL nickel foam into the mold to complete the three-layer structure of the battery; The three-layer battery was pressed for 90 seconds using a tablet press to obtain the desired single cell.
[0041] Composite electrolyte batteries with different proportions are obtained.
[0042] Performance Testing 1. XRD analysis was performed on the LDC, LAO3 and LDC-LAO3 composite materials obtained in Examples 1 to 3. The results are as follows: Figure 2 shown.
[0043] Figure 2 (a) Yes Ce 0.8 La 0.2 O 2-δ XRD diffraction pattern of the material sintered at 800℃ for 2h. 0.8 La 0.2 O 2-δ After sintering at 800°C for 2 hours, its diffraction peaks corresponded to those of CeO2 one by one, and no redundant diffraction peaks appeared, which proved that the present invention successfully achieved the preparation of electrolyte LDC materials.
[0044] Figure 2 (b) is the XRD spectrum of the LAO3 material synthesized by the sol-gel method after sintering at 1300 °C for 5 hours. As can be seen from the figure, the XRD diffraction peaks of the synthesized LAO3 electrolyte material are completely consistent with the positions of the diffraction peaks of the standard PDF card #85-0848, and no extra diffraction peaks appear. It proves that pure phase LAO3 electrolyte material can be obtained at this temperature.
[0045] Figure 2 (c) is the XRD diffraction pattern of the composite electrolyte material LAO3 and LDC mixed in different mass ratios. The two materials were physically mixed to prepare five dual-phase material mixing ratios of 5:5, 6:4, 7:3, 8:2, and 9:1. As can be seen from the figure, the XRD diffraction peaks of the composite electrolyte after physical mixing correspond to the XRD diffraction peaks of the single-phase material. At the same time, it can be seen that with the increase of the LAO3 doping ratio, the diffraction peak of LAO3 is more obvious, and the diffraction peak intensity of LDC is correspondingly reduced, indicating that the present invention successfully achieves the mixing behavior of the dual-phase material.
[0046] Figure 3 This is a SEM picture of the LDC material synthesized in Example 1. It can be seen that the LDC powder prepared in this example has a uniform morphology and is a nano-scale ultrafine powder.
[0047] 2. The single cell prepared in Example 5 is placed in a test fixture, and nickel foam of equal area is fixed on both sides of the cell as a support layer for collecting electrons.
[0048] The cross-sectional SEM images and contact surface SEM images of the single cell with a LDC to LAO mixing ratio of 7:3, i.e., 7LDC-3LAO3 composite electrolyte, after testing are analyzed. Figure 4 As shown; Figure 4(a) The three-layer structure of the battery can be clearly seen, with a composite electrolyte in the middle and NCAL symmetrical electrodes on both sides. The boundary between the electrode and the electrolyte is clear, and no chemical reaction occurs, indicating that the electrode and the electrolyte have good chemical stability.
[0049] Figure 4 (b) is the contact surface diagram of the battery's electrode and electrolyte. From the image, we can analyze that the loose and porous electrode is conducive to the diffusion and adsorption of gas, making it easier for fuel gas and air to participate in the redox reaction, while the denser electrolyte isolates the gas from penetrating. The electrode and electrolyte are in good contact, and no obvious cracks are observed. The thermal expansion coefficients of the two are similar, indicating good thermal matching. In summary, the composite material composed of LAO3 and LDC as a fuel cell electrolyte can ensure the normal power output of the battery under working conditions.
[0050] 3. Analysis of IV and IP characteristic curves of composite electrolyte batteries with different ratios tested at 550℃, 500℃, 450℃ and 400℃, as shown in the following figure: Figure 5 As shown; It can be seen from the figure that with the increase of the composite ratio of LAO3 material, the power output density of the battery first increases and then decreases. When the composite ratio is 7:3, the maximum power output is 1051 mW·cm at 550 ℃. -2 In addition, the power density when the doping ratio is 9:1, 8:2, 6:4, and 5:5 is 839 mW·cm -2 、939 mW·cm -2 、934 mW·cm -2 and 846 mW·cm -2 . The open circuit voltage of the composite electrolyte-supported fuel cell Ni-NCAL / 7LDC-3LaAlO3 / NCAL-Ni battery at 550 ℃ is about 1.126 V, which is significantly improved compared with pure LDC. The reason is that LAO3 is an ultra-wide bandgap oxide. The potential energy barrier generated at the heterogeneous interface of LAO3 and LDC plays an important role in inhibiting electron conduction. The potential energy barrier for electron transmission is large due to the composite ultra-wide bandgap oxide, which prevents the possibility of short circuit of CeO2 base in a reducing atmosphere, thereby achieving high OCV of the fuel cell. At the same time, due to the interface charge compensation, more oxygen vacancies are induced, which further promotes ion transmission, thereby obtaining high ionic conductivity and fuel cell performance.
[0051] As the operating temperature decreases, it can be clearly observed that the opening voltage of the battery with each composite ratio gradually increases, and the power output gradually decreases. This is because when the operating temperature decreases, the catalytic performance of the electrode will decrease significantly, and the ion transport performance of the electrolyte will also decrease significantly.
[0052] 4. The electrochemical impedance spectroscopy of batteries with different composite ratios tested at 550°C and the electrochemical impedance spectroscopy of 7LDC-3LAO3 tested at 550°C, 500°C, 450°C and 400°C respectively are analyzed. Figure 6 As shown; From the fitting results, it can be seen that among the ohmic impedances of the electrolyte batteries with different composite ratios at 550°C, the R0 of 7:3 is the smallest, which is 0.1667 Ω·cm 2 Its ohmic impedance first decreases and then increases with the compounding of LAO3 material. In LDC:LAO3=7:3, its R0 measured at 500 ℃, 450 ℃, and 400 ℃ in the cooling test is 0.2236 Ω·cm 2 , 0.3590 Ω·cm 2 , 0.4 Ω·cm 2 . It can be observed from the fitting results that both the ohmic impedance and the polarization impedance gradually increase. The increase in R0 is mainly due to the obstruction of ion and electron transmission caused by cooling, which makes ion transmission in the electrolyte difficult and increases the resistance of current passing through the electrolyte and the electrode. Rp is mainly related to the ion transmission rate and the gas diffusion rate. The reason for the increase in Rp is that the catalytic activity of the electrode decreases during the temperature reduction process, the diffusion rate of the gas slows down, and the exchange process between the reactants and the electrode is restricted.
[0053] 5. The ionic conductivity curves of 7LDC-LAO3 and pure LDC electrolyte with a mass ratio of 7:3 at 550℃, 500℃, 450℃, and 400℃ are analyzed. Figure 7 As shown; After the electrochemical performance test, the conductivity of the fuel cell is usually calculated to compare the electrochemical performance. The conductivity is estimated from the electrochemical performance output curve. The smooth part of the IV curve is called ohmic polarization, which represents the ohmic loss in the SOFC. The specific calculation formula is as follows:
[0054] Where L, R, and S represent the thickness of the electrolyte, impedance, and effective area of the battery, respectively. In this experiment, the thickness of the electrolyte was measured by SEM, and the effective area of the battery was fixed at 0.64 cm 2 The results show that the ionic conductivity of the composite electrolyte has been greatly improved. This further shows that the battery performance prepared by the LDC and LAO3 composite electrolyte is even better.
[0055] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0056] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A LDC-LaAlO3 composite electrolyte material, characterized in that: The composite electrolyte material is used as an electrolyte for a semiconductor ion fuel cell. The composite electrolyte material is obtained by mixing LDC and LAO3. The LDC is La 3+ The doped CeO2, the LAO3 is LaAlO3, and the mixing mass ratio of the LDC and LAO3 is 5~9:1~5.
2. The LDC-LaAlO3 composite electrolyte material according to claim 1, characterized in that: The LDC and LAO3 mixing mass ratio is 6-8:2-4; The La 3+ The proportion of doped CeO2 does not exceed 30%.
3. The method for preparing the LDC-LaAlO3 composite electrolyte material according to claim 1 or 2, characterized in that: The following steps are involved: (1) Preparation of LDC: Weigh the raw materials Ce salt, La salt and glycine; Mix Ce salt, La salt, glycine and water, heat and stir until the reaction liquid becomes viscous and finally produces powder with flame; collecting the powder, and sintering the powder to obtain LDC powder; (2) Preparation of LAO3: Weigh Al salt, La salt, EDTA and citric acid; Place Al salt, La salt, EDTA and citric acid in a container, add water, stir to dissolve, heat the water area and stir, adjust the pH value of the solution to 6-7, at which point the precipitate is completely dissolved; When the solution becomes viscous like a gel, it is dried, ground once, pre-calcined, ground twice, and sintered to obtain LAO3 powder. (3) Synthesis of LDC-LaAlO3 composite electrolyte materials Weigh LDC powder and LAO3 powder according to the mass ratio; The LDC and LAO3 materials were dissolved in ethanol, and then ball-milled, dried and ground to obtain the LDC-LaAlO3 composite electrolyte material.
4. The preparation method according to claim 3, characterized in that: In step (1), the Ce salt is Ce(NO3)3·6H2O, the La salt is La(NO3)3·6H2O, the molar ratio of glycine to metal ions is 1-1.5:1; and the metal ions are the sum of Ce ions and La ions.
5. The preparation method according to claim 3, characterized in that: In step (1), the heating temperature is 200-230°C, the sintering temperature is 750-850°C, and the sintering time is 1.5-3h.
6. The preparation method according to claim 3, characterized in that: In step (2), the Al salt is Al(NO3)3·9H2O, the La salt is La(NO3)3·6H2O, and the molar ratio of the sum of the Al ions and the La ions to the citric acid and EDTA is 1:1.5:1.
5.
7. The preparation method according to claim 3, characterized in that: In step (2), the water area heating temperature is 70-85°C; the drying temperature is 200-230°C, and the drying time is 4-6 hours; the pre-firing temperature is 450-550°C; the sintering temperature is 1200-1300°C, and the sintering time is 4-6 hours.
8. The preparation method according to claim 3, characterized in that: In step (3), the ball milling speed is 180-200 r / min, and the ball milling time is 4-6 h.
9. A semiconductor ion fuel cell comprising the LDC-LaAlO3 composite electrolyte material according to any one of claims 1 or 2.
10. The semiconductor ion fuel cell according to claim 9, characterized in that: The electrode material of the semiconductor ion fuel cell is LiNi 0.8 Co 0.15 Al 0.05 O2, LiNi 0.8 Co 0.15 Al 0.05 O2 is mixed with pinene alcohol, alcohol and PVB to obtain NCAL slurry, which is then applied to nickel foam to obtain the electrode of the semiconductor ion fuel cell.
